Analysis the effect of Islamic Bank Financing on The Human Development Index (a Case Study of 15 Cities on Java Island in 2015-2021) - Hanifa Salsabila (Program Pascasarjana Universitas Islam Negeri Sunan Kalijaga, 2022)
et,1/ida,c.1